The Correlation Between Primary Care Nurses' Nutritional Knowledge And Self-Management Quality Among Type 2 Diabetes Patients (The Review of Diabetic Studies, 2025)
Background: Primary​‍​‌‍​‍‌​‍​‌‍​‍‌ care nurses are the main drivers of the diabetes management education team. Yet, the relationship between nurses' knowledge of nutrition and the self-management results of patients remains ambiguous in primary care settings. Objective: To find out the relationship between a primary care nurse's knowledge of nutrition and the self-management quality of Type 2 Diabetes (T2D) patients. Method: Cross-sectional study of 187 nurses and their 1247 T2D patients from 12 primary care clinics. The nutritional knowledge of the nurses was measured by the validated Diabetes Nutrition Knowledge Test (DNKT, α=0.87). Patient self-management was measured by the standard Summary of Diabetes Self-Care Activities (SDSCA) scale. The interaction between nurse-level and patient-level variables was assessed by hierarchical linear modeling. Result: Nutritional knowledge of nurses was strongly associated with the quality of self-management of patients (r=0.512, p